Women in management, champions of change : papers presented at the Third Academic Conference of Management Development Institutions in South Asia (AMDISA) : February 7, 1994 Dhaka, Bangladesh - Sogra, Khair Jahan (University Press, 1994)
With special reference to South Asia.